Transcultural adaptation to Brazilian Portuguese and reliability of the effort-reward imbalance in household and family work - Ilmeire Ramos Rosembach de Vasconcellos; Rosane Härter Griep; Luciana Portela; Márcia Guimarães de Mello Alves; Lúcia Rotenberg (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To describe the steps in the transcultural adaptation of the scale in the Effort-reward imbalance model to household and family work to the Brazilian context. METHODS We performed the translation, back-translation, and initial psychometric evaluation of the questionnaire that comprised three dimensions: (i) effort (eight items, emphasizing quantitative workload), (ii) reward (11 items that seek to capture the intrinsic value of family and household work, societal esteem, recognition from the spouse/partner, and affection from the children), and (iii) overcommitment (four items related to intrinsic effort). The scale was included in a sectional study conducted with 1,045 nursing workers. A subsample of 222 subjects answered the questionnaire for a second time, seven to 15 days thereafter. The data were collected between October 2012 and May 2013. The internal consistency of the scale was evaluated using Cronbach's alpha and test-retest reliability analysis, square weighted kappa, prevalence and bias adjusted Kappa, and intraclass correlation coefficient. RESULTS Prevalence and bias-adjusted Kappa (ka) of the scale dimensions ranged from 0.80-0.83 for overcommitment, 0.78-0.90 for effort, and 0.76-0.93 for reward. In most dimensions, the values of minimum and maximum scores, average, standard deviation, and Cronbach's alpha were similar in test and retest scores. Only on societal esteem subdimension (reward) was there little variation in standard deviation (test score of 2.24 and retest score of 3.36) and in Cronbach's alpha coefficient (test score of 0.38 and retest score of 0.59). CONCLUSIONS The Brazilian version of the scale was found to have proper reliability indices regarding time stability, which suggests adapting it to be used in population with characteristics that are similar to the one in this study.